The effectiveness of using story-based pop-up book media on the speaking skills of children aged 5-6 years in the Pembina Padang State Kindergarten - Maida Yanti, Chika; Yulsyofriend, Yulsyofriend (Tunas Siliwangi, 2024)
This research was motivated by the problem of children's lack of speaking skills which have not yet developed optimally. There are various ways that can be done to develop children's speaking skills through telling stories using media that can attract children's attention, such as using pop-up book media using test and observation data collection techniques. The aim of this research is to find out how effective the use of pop-up book media is on children's speaking skills. This research uses quasi-experiment as a quantitative method. The population of this study was all children in the Pembina Padang State Kindergarten, while the sample was 14 children in each class B1 and B2. The average pre-test score of the experimental group was 9.57 and the average post-test score was 19.07. The average pre-test score for the control group was 10.50, while the average post-test score was 15.00. The final data set from the effect size test shows a value of d > 1.00, with a value of d=14.42 which is classified as strong, which means that the use of story-based pop-up book media is effective in improving the speaking skills of young children.